The impact of EU institutional advertising on public support for European integration - Hernández, Enrique (2020)
Utilitarian theories propose that support for the EU is based on an instrumental calculus about the costs and benefits of European integration. Drawing on these theories, we analyze whether and how ads produced by European institutions affect public support for the EU. Our findings, based on a panel survey experiment, indicate that these ads increase support for the EU, and that ads emphasizing the policy benefits of European integration are more effective than ads emphasizing its reduced costs. However, these positive effects are short-lived, since they had disappeared one year after citizens were initially exposed to the ads. In a context of increasing negativity towards the EU, these findings, based on realistic treatments, have relevant theoretical and policy implications.